PERILAKU MEMILIH PEMULA DALAM PILPRES 2024: STUDI KASUS KECAMATAN CENGKARENG, JAKARTA BARAT - Abror Torik Tanjilla (Universitas Muhammadiyah Jakarta, 2025)
Party identification was the most consistent factor, meaning that strengthening identification that was not aligned with the reference pair correlated with a decrease in the likelihood of voting for that pair. This was the main finding of this study. This study aimed to examine the voting behavior of first-time voters in the 2024 Presidential Election in Cengkareng using binary logistic regression. Substantive results indicate that party affiliation is the primary factor driving young voters to political choices. There was no evidence that the results were directly influenced by family and environmental factors, as well as by profit and loss calculations. There were differences in education, employment status, and geographic location, according to the control variables. Practically, a communication approach centered on increasing partisan affiliation and identity through tailoring sociodemographic and regional contexts is more prospective for reaching first-time voters. Keywords: first-time voters, voting behavior, 2024 presidential election, Cengkareng